The Effect of Institutional Ownership and Dividend Policy on Company Value with Quality Earnings as an Intervening Variable - Yuppy Triwidatin; Dendi Afrian (MultiTech Publisher, 2023)
The study is to determine the effect of institutional ownership and dividend policy on corporate value with earnings quality as an intervening variable in manufacturing companies listed in Indonesia Stock Exchange (IDX) for 2012-2016. The population in this study is 162 manufacturing companies. Sampling totaling 27 companies was done by purposive sampling. Data analysis methods used in this research are descriptive statistical analysis, classical assumption tests, fit model tests and Structural Equation Modeling (SEM) analysis. The results of this study indicate that: (1) Institutional ownership doesn't have an impact on profit quality with a significant value of 0.955 (0.955> 0.05), (2) Dividend policy has a positive and significant impact on profit quality with a significant value 0.032 (0.032 ≤ 0.05 ), (3) Institutional ownership has a positive and significant impact on corporate value with a significant value *** (<0.01) or (*** ≤ 0.05). (4) Dividend policy has a positive and significant impact on corporate value with a significant value *** (<0.01) or (*** ≤ 0.05), (5) Profit quality has a positive and significant impact on corporate value with a significant value 0.019 (0.019 ≤ 0.05), (6) Profit quality as intervening variable between institutional ownership on company value with a significant value 0.026 (0.026 ≤ 0.05), (7) Profit quality not as intervening variable between dividend policy on corporate value with a significant value 0.571 (0.571> 0.05)